Locally Preferred Woody Species and Their Management in Kiruhura and Arua Districts, Uganda - Nyamukuru, Antonia; Nabatanzi, Alice; Mpiira, Sam; Tabuti, John R.S. (Ethnobotany Research and Applications, 2015)
<!–[if gte mso 9]> 1024x768 <![endif]–> Trees and shrubs are disappearing fast in anthropogenic landscapes of Uganda. In order to promote their conservation on-farm, there is need to involve farmers. Farmers’ involvement in tree/shrub management requires a clear understanding of the households’ needs that trees can satisfy, the priority species to satisfy these needs, as well as tree management practices and challenges that hinder tree planting. This study was carried out to satisfy these information needs and to also determine species that are locally threatened. The study was conducted in selected villages of Arua and Kiruhura districts between June and October 2012 using an ethnobotanical approach. Our results indicate that farmers value tree products to satisfy household welfare needs of accessing food (edible fruits), generating income, and accessing construction wood. The species are multi-purpose, and the most preferred are Eucalyptus spp., Mangifera indica L., Persea americana Mill., Carica papaya L., Citrus limon (L.) Osbeck, Artocarpus heterophyllus Lam., Citrus sinensis (L.) Osbeck, Annona senegalensis Pers., Pinus spp., and Tectona grandis L.f. Most farmers maintain trees on their land in courtyards, backyard gardens, or crop fields and ranches. Tree species are threatened by destructive harvesting and clearing land for agriculture. The key challenges to intensification of tree cultivation are livestock damage, land shortage, drought, and lack of financial resources. Farmers suggested that in order to strengthen tree planting, they should be provided with inputs including seedlings, chemicals, and tools. In conclusion farmers prefer exotic tree species to satisfy household needs. Intensification of tree management will need to address a number of challenges identified in this study. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>